Peranan Teman Sebaya dalam Orientasi dan Mobilitas Lingkungan Sekolah pada Siswa Tunanetra di SMKN 7 Padang - Ayu Ermayuni; Fatmawati Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2019)
The problem examined in this study is the role of peers who are intended as an alert companion to the environment and mobility in the school environtment for blind students. This study aims to describe the implementation of relationships and mobility, what happens and how to solve problems. This study uses a qualitative descriptive method. Universal distributed data techniques, interviews, and documentation. The results of the study indicate that peer assignments and travel as a companion help in giving directions or direction to blind students. Constraints related to road conditions, stairs and mastery of techniques. An attempt is made to give an injection first. So it can be concluded that there is still a lack of mastery of techniques by blind or alert students.